Ekstrakurikuler Pramuka Untuk Membentuk Karakter Siswa Sekolah Dasar - Windy Antika; Ratih Ayunda; Wahyuni Amanda Hasibuan; Monica Gabriela Nainggolan (Pusat Riset dan Inovasi Nasional, 2024)
Character training is a significant part in the advancement of moral schooling. Exploring training plays a significant part in molding the personality of understudies, particularly grade school understudies. Scout extracurriculars can assist understudies with creating mental, emotional and psychomotor abilities, as well as structure characters like discipline, participation, initiative, love of the nation and useful abilities. The expect to be accomplished is to figure out the job of scout extracurricular exercises in forming the personality of grade school understudies. The examination strategy utilized is library study or writing is one of the exploration methodologies utilized and considered. Scouting activities can assist students in developing responsible character, such as an awareness of responsibility and the capacity to make the right decisions. Scouting activities play an important role in forming students' social care character, such as concern for society and awareness of the environment.